Strategic arbitrage in segmented markets - Bryzgalova, Svetlana; Pavlova, Anna; Sikorskaya, Taisiya (Journal of Financial Economics, 2025)
We propose a model in which arbitrageurs act strategically in markets with entry costs. In a repeated game, arbitrageurs choose to specialize in some markets, which leads to the highest combined profits. We present evidence consistent with our theory from the options market, in which suboptimally unexercised options create arbitrage opportunities for intermediaries. We use transaction-level data to identify the corresponding arbitrage trades. Consistent with the model, only 57% of these opportunities attract entry by arbitrageurs. Of those that do, 49% attract only one arbitrageur. Finally, we detail how market participants circumvent a regulation devised to curtail this arbitrage strategy.